PECULIARITIES OF THE PROCESS OF DIGITALIZATION OF THE COMMUNICATIVE COMPONENT IN THE ACTIVITY OF PUBLIC AUTHORITIES - DOROFYEYEV, Oleksandr; DUBYNKA, Oleh (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Due to the constant development of technology and rapid digital progress in today’s world, digitalization in public administration communication is very important. Researching its features is essential in developing a modern state and improving the quality of public services for citizens. Despite numerous studies on this topic, it should be emphasized that the specifics of digitalization’s impact on ensuring the efficiency, transparency, and accessibility of public services and the development of Ukraine’s digital transformation are still not sufficiently disclosed and require further elaboration. This study aims to determine the main features of the digitalization process in public administration communication in modern conditions. The main feature of digitalization in the communication of public administration in Ukraine is its unique blend of technological development and societal needs. This research highlights a key aspect of this process - the introduction of electronic services and online platforms, which play a pivotal role in ensuring the accessibility and convenience of services for citizens. Based on the research results, the leading digitalization technologies used in public administration to provide public services are singled out: cloud computing, artificial intelligence, the Internet of Things, and big data analytics. These technologies’ role in modernizing public services, increasing efficiency, and improving citizens’ general experience is clarified. It has been proven that efficiency, transparency, and convenience are the possibilities that should accompany digitalization in the communication of public administration in Ukraine. Problematic issues and risks of the digitization process in public administration communication are outlined, among which should be presented: lack of developed digital skills of public servants, cost, cyber threats, different capabilities of territorial communities (digital inequality), and dependence on light and the Internet.